The Monitoring and Evaluating System of Implementation of Provincial Health System Development - Kietmetha, Virach; Akharasuwankul, Anan (Journal of Health Science of Thailand, 2018)
This research was aimed at developing the monitoring and evaluating system of strategic implementation of provincial health system development and the public hearing of Trang stakeholders by using research and development process (R&D) and participatory action research (PAR). The study was divided into two phases. The first phase, developing the system, consisted of four steps: 1) creating the monitoring and evaluating criteria, 2) developing the information system to serve the monitoring and evaluating process, 3) using the monitoring and evaluating system, and 4) applying the evaluation results into management. The second phase was public hearing of stakeholders. The methods used in this section were in-depth interview of 5 groups of administrators and academics (10 subjects altogether) and Future Search Conference (FSC) of the 2 groups of subjects comprising 27 participants. The findings revealed that the monitoring and evaluating criteria were divided into two parts: the monitoring and evaluating of plan/project implementation under the strategic plan of health system development and the evaluating of objectives and goals indicators with 5 success levels. The developed information system could be used to monitor and evaluate in four levels: 1) strategic goal and objective level, 2) strategy level, 3) project level that could monitor input factors, outputs of major activities and outcomes of project objectives, and 4) success level in working of working groups and individuals. The use of monitoring and evaluating system resulted in having extra organizational bodies in addition to the planning and evaluating committee of Office of Provincial Public Health. The new additional structure comprised the planning and evaluating sub-committee, the monitoring and evaluating committee, and the coordinating committee for implementation of strategic plans. Each committee/sub-committee needed to relate to each other. With reference to public hearing result, the stakeholders viewed that the monitoring and evaluating system was essential and suitable to be applied in the changing circumstances. Moreover, the system was in line with Public Sector Management Quality Award (PMQA).